Modifications in magnetic anisotropy of M-type strontium hexaferrite crystals by swift heavy ion irradiation - Kaur, Balwinder; Bhat, Monita; Licci, F.; Kumar, Ravi; Kulkarni, S. D.; Joy, Pattayil Alias; Bamzai, K. K.; Kotru, P. N. (Journal of Magnetism and Magnetic Materials, 2006)
Using vibrating sample magnetometery (VSM) 50 MeV Li(3+) ion irradiation effects on magnetic properties of single crystals of SrGa(x)In(y)Fe(12-(x+y))O(19) (where x = 0, 5, 7, 9; y = 0, 0.8, 1.3, 1.0), are reported. The substitution of Ga and In in strontium hexaferrite crystals decreases the value of magnetization sharply, which is attributed to shifting of collinear magnetic order to a non-collinear one. Reduction of magnetization is also explained to be as a result of the occupation of the crystallographic sites of Fe(3+) by Ga(3+) and In(3+). The Li(3+) ion irradiation decreases the value of magnetization, irrespective of whether the crystals are Ga-In substituted or unsubstituted crystals of SrFe(12)O(19). The result is interpreted in terms of the occurrence of a paramagnetic doublet in crystals replacing magnetic sextuplet as a result of irradiation. Substitution of Ga-In in Strontium hexaferrite decreases the value of anisotropy constant. Irradiation with Li(3+) ions increases the values of anisotropy field for both substituted as well as unsubstituted crystals. Substitution with Ga-In also decreases the Curie temperature (T(c)) but the irradiation with Li(3+) ions does not affect the curie temperature of either Ga-In substituted or pure SrFe(12)O(19) crystals. (C) 2006 Elsevier B.V. All rights reserved.
Keywords: anisotropy field; Curie temperature; irradiation; Magnetic anisotropy; Magnetization

Mapping the finite-temperature behavior of conformations to their potential energy barriers: case studies on Si6B and Si5B clusters - Maneri, Asma H.; Singh, Chandrodai Pratap; Kumar, Ravi; Maibam, Ashakiran; Krishnamurty, Sailaja (ACS Omega, 2022)
Dynamical simulations of molecules and materials have been the route to understand the rearrangement of atoms within them at different temperatures. Born-Oppenheimer molecular dynamical simulations have further helped to comprehend the reaction dynamics at various finite temperatures. We take a case study of Si6B and Si5B clusters and demonstrate that their finite-temperature behavior is rather mapped to the potential energy surface. The study further brings forth the fact that an accurate description of the dynamics is rather coupled with the accuracy of the method in defining the potential energy surface. A more precise potential energy surface generated through the coupled cluster method is finally used to identify the most accurate description of the potential energy surface and the interconnected finite-temperature behavior.